Mare milk fatty acids with reference to donkey, cow, goat and human milk - Orlandi, Mario; Contarini, Giovanna; Cattaneo, Tiziana MP; Curadi, M. Claudia (Progress in Nutrition, 2014)
Trials were carried out on 6 Noriker (N),12 Thoroughbred (TH), 38 Haflinger (H) and 9 Amiata donkeys milk samples collected at 30, 60 and 90 days from delivery. FA profile was investigated referring mainly to linoleic acid (LA), α-linolenic acid (ALA), LA/ALA ratio and saturated/unsaturated ratio. LA content was higher in Thoroughbred milk samples at 30, 60 and 90 days. LA/ALA ratio was 0.51, 0.49, 0.39 in Noriker samples at 30, 60, 90 days with a saturated/unsaturated ratio about 1. In Thoroughbred milk samples saturated/unsaturated ratio was 0.87, 0.71, 0.57 and in Haflinger samples 1.24, 1.09, 1.29 respectively at 30, 60, 90 days after delivery. Investigations concerned also milk FA content from Haflinger, Noriker ,Thoroughbred and Amiata milk samples collected at 60 lactation days compared with cow, goat and human milk collected at the same time. Unsaturated FA were found about 55% in mare samples, higher than cow and goat (33.49%-30.21%) and similar to human milk (54.62%). Lower levels (25.13%) were found in Amiata samples. All mare samples were rich in LA (6.22%-15.41% FA) and ALA (7.88%-12.50%). In human milk LA and ALA were 13.54% and 1.02%, respectively; LA and ALA content was high also in donkeys samples (8.17% and 6.69%) and lower in goat (2.62% and 0.63%) and in cow (1.86% and 0.57%). Saturated/unsaturated ratio range was between 0.70 and 1.09 in different horses breed samples, 3.04 in Amiata 2.30 ratio was observed in goat samples, 1.88 and 0.83 respectively in cow and in human milk samples.